THE WEIGHT OF BEING: EXISTENTIAL CRISIS IN ANEES SALIM’S FLY HASINA, FLY - Prasath, V. Niranjan; S. Mangaiyarkarasi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the existential crisis of Hasina, the protagonist of Anees Salim’s Fly Hasina, Fly, whose life as a coffee vending machine attendant at an airport becomes a microcosm of late capitalist alienation. Trapped in a monotonous routine, burdened by familial obligations, and subjected to systemic abuse, Hasina’s psychological deterioration reflects what philosopher Albert Camus termed “the absurd”, the confrontation between human desire for meaning and the universe’s indifference. Through a synthesis of existentialist philosophy of Camus, Sartre, Federici, Berlant, and trauma theory of Herman Judith, this essay argues that Hasina’s suffering is not merely personal but emblematic of the subaltern woman’s condition under neoliberalism. This paper explores how these forces coalesce into an existential crisis, one where Hasina’s struggle is not just against poverty, but against the crushing weight of meaninglessness.